Accuracy improvement of the immersed boundary–lattice Boltzmann coupling scheme by iterative force correction. (2nd January 2016) - Zhang, Chunze; Cheng, Yongguang; Zhu, Luoding; Wu, Jiayang
Highlights: An iterative force correction for the IB–LB scheme is proposed. Instead of the delta function, the Lagrange interpolation is used to obtain the IB speed. The non-slip boundary conditions can be enforced accurately at the IB points. A mechanical heart valve flow is simulated. Better agreements with experimental data are achieved. Abstract: The non-slip boundary condition at solid walls cannot be accurately achieved by the conventional immersed boundary–lattice Boltzmann (IB–LB) coupling schemes due to insufficient interpolation accuracy. To solve this problem, an iterative force correction procedure for the IB–LB coupling scheme is proposed. Cheng's external forcing term in the LB equation is selected to properly incorporate the present and the next time step effects. The unknown IB force and the corresponding force on fluid at the next time step are calculated by iterative correction, based on the known immersed boundary speed, flow velocity, and the relationship between the IB speed and the IB force. Instead of the Dirac delta function, the Lagrange interpolation polynomial is used to obtain the IB speed from nearby fluid velocity. Typical cases, including the flow around a circular cylinder, shearing flow near a non-slip wall, and circular Couette flow between two inversely rotating cylinders, are simulated to verify and validate the method. It is shown that the present method guarantees the non-slip boundary condition and maintain the overall first-order spatial convergence rate of the conventional immersed boundary method (IBM). The accuracy improvement is obvious for both stationary and moving solid boundaries in both viscous flows and strong shearing flows. To demonstrate application possibility, a mechanical heart valve flow is also simulated, and better agreements with experimental data are achieved compared to those by commercial software.